THE EFFECT OF OOCYTE DEVELOPER (OODEV)ON GONAD MATURATION OF SHEAT FISH (Ompok rhadinurus Ng) - Fitri Rahmayani Tambunan; Netti Aryani; Hamdan Alawi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbtraksThe effect % Oocyte Developer (Oodev) dose on gonad find maturation % sheat fish (Ompok rhadinurus Ng) was conducted from July to October 2019 at the Aquaculture Research station, Faculty of Fisheries and marine, University of Riau. Pond raised brords takes weight ranged from 35 g to 42 g were injected with different doses % Oodev : P0 (0 ml/kg fish); P1 (0,5 ml/kg), P2 (1 ml/kg) and P3 (1,5 ml/kg) and raised for maturation in 0,5 m2 cages. The Oodev injection were done every 7 days. The results that Oodev dose effected the gonad maturation of sheat fish the dose % 1,5 ml/kg was the best result : duration of maturation wn 24 days; number of egg stripping 109 egg/gram fish; ovisomatic index 14,14%; egg diameter 1,27 mm; fertilization rate 89,30%; hatching rate 90,67% and survival rate % 5 days was 95,16%. Water quality parameters during experiment were classified as optimal, 23 – 27,4oC of temperature, 6,0-7,2 of power of hydrogen (pH) and 4,5 – 5,6 mg/l of dissolved oxygen.                                                                                     Keywords : Sheat fish, Oodev hormone, Gonad maturation, dose